2022
DOI: 10.1007/s11627-022-10301-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting in vitro regeneration in the model tree Populus trichocarpa I. Medium, environment, and hormone controls on organogenesis

Abstract: In preparation for a major GWAS (Genome Wide Association Study) of plant regeneration and transformation, a large number of factors were examined for their effects on indirect regeneration rate in diverse wild genotypes—seeking a high rate of regeneration, but also highly genetically variable and heritable treatments. Many of the factors examined have never before been reported on for their effects on callus, shoot, or root organogenesis in poplar (Populus). Stems had the highest regeneration potential, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…A regeneration study on Andrographis echioides demonstrated that the maximum regeneration efficiency and number of regenerations were achieved when the 6-BA/IAA ratio was 15/1 ( Savitikadi et al., 2020 ). For Populus trichocarpa , a cytokinin/auxin ratio of 5/1 resulted in the highest bud induction rate ( Ma et al., 2022 ). However, the specific ratios and intensities of these hormones have not been clearly determined across different plants, and varying these ratios with different hormone strengths can lead to dramatically different outcomes ( Song et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…A regeneration study on Andrographis echioides demonstrated that the maximum regeneration efficiency and number of regenerations were achieved when the 6-BA/IAA ratio was 15/1 ( Savitikadi et al., 2020 ). For Populus trichocarpa , a cytokinin/auxin ratio of 5/1 resulted in the highest bud induction rate ( Ma et al., 2022 ). However, the specific ratios and intensities of these hormones have not been clearly determined across different plants, and varying these ratios with different hormone strengths can lead to dramatically different outcomes ( Song et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Populus trichocarpa represents an ideal model to study in vitro TR in a GWAS context due to a wealth of genomic resources, as well as detailed in vitro culture (Kang et al ., 2009; Ma et al ., 2022a,b) and transformation methods (Han et al ., 1997; Ma et al ., 2004; Song et al ., 2006; Li et al ., 2015). A diverse population of 1323 re‐sequenced poplar clones, collected from across its natural range in northwestern North America, provides high levels of genetic diversity and statistical power for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Competing and antagonistic roles of JA/ethylene and SA likely evolved in response to a need for distinct defense mechanisms against biotrophic and necrotrophic pathogens, in both cases with precise control of necrosis of infected and nearby tissues being essential for the plant to contain infection (Spoel et al ., 2007). In the context of in vitro regeneration, the wounding of explants (excised plant tissues) may lead to either necrosis or regeneration at the site of wounding, with the patterns of necrosis and regeneration being highly genotype‐dependent, including in poplar (Ma et al ., 2022a,b). Moreover, a third key phytohormone axis involves the competitive actions of gibberellins and abscisic acid (ABA), often studied in the context of their roles in seed and vegetative development, as well as in abiotic stress response (Shu et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%